SELF-SIMILAR TRAFFIC GENERATOR - Linawati, Linawati; Suartika, I Made (Majalah Ilmiah Teknologi Elektro, 2005)
Network traffic generator can be produced using OPNET. OPNET generates the traffic as explicit traffic or background traffic. This paper demonstrates generating traffic in OPNET 7.0 as background traffic. The traffi generator that was simulated is self-similar traffic with different Hurst parameter. The simulation results proved that OPNET with background traffic function can be as a qualified self-similar traffic generator. These results can help in investigating and analysing network performance for self-similar traffic input